Experimental laser-machining of silicon wafer - Lau, Zhen Chyen (2010)
This thesis deals with laser machining of silicon wafer at various process parameters. The objective of this thesis is to investigate the effect of laser machining parameters on the cut surface quality and determine the feasible laser machining parameters that can machine silicon wafer. The thesis describes how machining parameters and air assist gas affects cut surface quality. The silicon wafer was machined by laser with and without air assists. Principally, two experimental sets with different cutting speed and laser power were designed in statistical software. The kerf widths and quality were observed under microscopes. The results then were analyzed using statistica software. The analysis indicated that cutting speed has significant effect to the kerf width and laser cutting with air assists produced wider kerf. Result obtained also showed that laser cutting without air assists produced better cut surface quality. The feasible machining parameter of silicon is estimated at 1.0-2.0 mm/min for cutting velocity, 0.80-0.94 watt for laser power in laser cutting without air assist and 1.0-4.0 mm/min for cutting velocity, 0.80-0.90 watt for laser power in laser cutting with air assist.